THE PERFORMANCE OF COCONUT SUPPLY CHAIN IN KUBU RAYA DISTRICT - M. Alfaliansyah; Maswadi Maswadi (JSEP (Journal of Social and Agricultural Economics), 2021)
The particular problem of coconut in Kubu Raya Regency is the ongoing partnership with suppliers to meet dynamic market changes that have not been well established. Supply chain management has become an important matter in the coconut industry in Kubu Raya Regency. Measurement of the performance of the coconut industry supply chain in order to optimize the performance of the coconut supply chain in Kubu Raya Regency, so that the realization of an efficient and effective coconut supply chain. Measurement of added value is done using the Hayami method and performance measurement is done by the SCOR method. The result of value added analysis shows that the added value of coconut in the farmer level is 758 rupiah / fruit. Analysis of supply performance using the SCOR method shows the performance of each member of the supply chain. Farmers have a 72.3% performance value included in the category below average. Traders and collectors obtained a performance value of 55.7% included in the Poor category.